Komunikasi Interpersonal dalam Membangun Hubungan untuk Meningkatkan Loyalitas Konsumen Brand Serahinke.Aku Bouquet - Putri, Fitria Novita; Nurchayati, Zulin; Sejati, Veny Ari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the application of interpersonal communication in building relationships between business owners and consumers and its contribution to consumer loyalty to the Serahinke.aku Bouquet brand. This study uses a qualitative approach with a descriptive case study method. The research subjects consisted of business owners and consumers of Serahinke.aku Bouquet who were selected based on their involvement in the communication and transaction process. Data were collected through in-depth interviews, observations of digital interactions, and documentation of communication on social media and instant messaging applications. Data analysis used the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Joseph A. DeVito's five dimensions of interpersonal communication play a role in building consumer loyalty. Openness builds trust through clear information, empathy strengthens understanding of consumer needs, support creates responsive service, a positive attitude builds comfortable interactions, and equality strengthens personal relationships between business owners and consumers. The application of these five dimensions contributes to consumer loyalty demonstrated through repeat purchases and recommendations. This study provides practical implications for the development of digital-based creative business communication strategies